The Concept and Essence of the Right to Inviolability of Personal Image (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the modern world, where images of people are easily replicated and distributed, the right to inviolability of personal image becomes more and more relevant. The article provides a comprehensive analysis of the concept and essence of the right to inviolability of personal image. The methods of comparison, prediction, analysis, deduction, synthesis are used to achieve the purpose of the research.The article offers a new vision of the essence of the right to inviolability of personal image, and formulates a number of proposals to improve the legislation of Uzbekistan in this area. The results of the research can be used for further development of the theory of law, as well as for improvement of legislation on personal data protection.